Guidance and Counseling Service Management in the Development of Anti-Bullying Program: Transformation from Bystander to Upstander - Margaretha Mega Natalia; Uman Suherman; Ibrahim Al Hakim (Ma'soem University, 2026)
The phenomenon of bullying in vocational schools remains a serious challenge in creating a safe and inclusive school climate. One factor that strengthens the sustainability of bullying behavior is the low active role of students as bystanders who tend to remain silent or allow bullying to occur. This study aims to develop a management model for guidance and counseling (BK) services in an anti-bullying program that focuses on transforming the role of bystanders into upstanders. The research method used a focus group discussion (FGD) approach at SMKN 3 Cimahi. Data were collected through in-depth interviews and documentation studies of BK teachers. The results show that the effectiveness of the anti-bullying program is highly dependent on the managerial skills of BK teachers in planning programs based on student needs, implementing group guidance services with an experiential learning approach, and continuous evaluation through cross-school collaboration. Experience-based interventions have been shown to increase students' awareness of empathy and sense of social responsibility in preventing bullying. This study recommends strengthening the capacity of data-based and collaborative BK service management as a key strategy to create a proactive and caring school culture.